Resepsi Tafsir Q.S. Al-Mujādilah di Tik-Tok sebagai Upaya Edukasi dan Pembelaan Hak-hak Perempuan - Althaf Husein Muzakky; Faisal Haitomi; Maula Sari (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
Tik-Tok is a medium that can educate various kinds of worldviews, such as social, political, legal, and religious issues. Through tik-tok content, people get the strengthening of Islamic values and gender in the QS interpretation video. Al-Mujādilah who fought a lot for women's rights, but not all videos circulating on tik-tok were not always true and valid, not even a few were patriarchal biased. This article aims to describe the reception of the interpretation of the Q.S. Al-Mujādilah on tik-tok as an effort to educate and defend women's rights. The research method was carried out with a qualitative approach where data collection was carried out by observing the tik-tok content and documenting the community's response. The results of this study indicate that tik-tok with the FYP algorithm has full power as social criticism to form a contextual religious understanding, conflict resolution, the study of Islamic issues and gender are packaged freshly as a new face that Islam is friendly to rights women.